2015
DOI: 10.1002/2014jd022371
|View full text |Cite
|
Sign up to set email alerts
|

Subtropical and midlatitude ozone trends in the stratosphere: Implications for recovery

Abstract: We present a comprehensive analysis of the trends of stratospheric ozone in the midlatitudes and subtropics. The analysis is performed using ground-based and space-based measurements over the light detection and ranging stations for the period 1985-2012. Also, trends are estimated for the zonal mean data made from a merged satellite data set, Global OZone Chemistry And Related trace gas Data records for the Stratosphere, over 1979-2012. The linear trends in stratospheric ozone are estimated using piecewise lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 50 publications
7
28
0
Order By: Relevance
“…Most studies consider either piecewise linear trends (PWLTs) or the equivalent effective stratospheric chlorine (EESC) proxy to represent the influence of hODSs on long-term ozone changes (Newman et al, 2007). Chehade et al (2014) and Frith et al (2014) both concluded that total column ozone trends up to 2012 and 2013 estimated from PWLTs or EESC prior to 1997 agree well, but post-1997 the EESC proxy implies significant and positive increases, while PWLTs are generally smaller and non-significant at most non-polar latitudes.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Most studies consider either piecewise linear trends (PWLTs) or the equivalent effective stratospheric chlorine (EESC) proxy to represent the influence of hODSs on long-term ozone changes (Newman et al, 2007). Chehade et al (2014) and Frith et al (2014) both concluded that total column ozone trends up to 2012 and 2013 estimated from PWLTs or EESC prior to 1997 agree well, but post-1997 the EESC proxy implies significant and positive increases, while PWLTs are generally smaller and non-significant at most non-polar latitudes.…”
Section: Introductionmentioning
confidence: 96%
“…Concentrations of active stratospheric hODSs reached a maximum in ∼ 1997 (Newman et al, 2007), and vertically resolved satellite measurements show evidence that upper stratospheric ozone (10-1 hPa; ∼ 32-48 km) started recovering soon after (WMO, 2014). Figure 1 presents post-1998 ozone changes from four ozone composites that combine multiple satellite instruments (see Sect.…”
Section: Post-1997 Ozone Changes Resolved By Latitude and Altitudementioning
confidence: 99%
See 2 more Smart Citations
“…WMO (World Meteorological Organization), Scientific Assessment of Ozone Depletion (2018) has reported that the upper stratospheric ozone has increased from 1995 to 2016. However, ozone in the lower stratosphere still showed a continuing declining trend (Ball et al, 2017(Ball et al, , 2018Gebhardt et al, 2014;Kyrölä et al, 2013;Nair et al, 2015;Sioris et al, 2014;Vigouroux et al, 2015;Zhang et al, 2018). In addition to trends, the interannual variations in lower stratospheric ozone also require detailed investigations, since the changes in lower stratospheric ozone can significantly influence climate change (Forster et al, 1997;Hu et al, 2015;Polvani et al, 2017).…”
Section: Introductionmentioning
confidence: 99%